Organizar la contabilidad en el comercial “Montaño y Compañía” del Sr. Montaño Pereira Rolando David, del cantón Macará, período del 01 de abril al 30 de junio de 2023 - Gomez Cordova, Jahely Camila (2024)
The Curricular Integration Work was developed with the purpose of applying an accounting organization to the commercial one, in order to know its economic-financial situation that contributes to decision-making. In order to achieve the objectives, it was framed in the specific laws, rules and regulations that govern the accounting process. The approach of the work is qualitative-quantitative of exploratory-descriptive type and non-correlational design since the economic facts were observed and after their analysis noted in the accounting records. In the execution of the results, the plan and manual of accounts were developed according to the model established by the Superintendence of Companies and coupled to the activity of the company. The physical verification of the goods, rights and obligations was carried out to determine the monetary values with which the accounting process was started, it should be noted that the inventory control was developed through the multiple account method. For an easy handling and better appreciation, purchase and sale auxiliaries were developed, as well as accounts payable and accounts receivable, as well as the roles of payments and provisions. The accounting process began with the preparation of the Statement of Initial Situation structured by Assets, Liabilities and Equity, with the source documentation, the memorandum of operations was developed, the transactions and majorization were made, and then the balance of sums and balances were made, then the accounts were transferred to the worksheet and the regularization and adjustment entries were recorded. Finally, the financial statements are developed with the information obtained. The information obtained from the Income Statement for the period April - June presents a net profit for the period of $5,955.55, the Statement of Financial Position shows a decrease in Accounts Receivable and Accounts Payable due to the proper management performed by the manager.